Watts in the Desert: Pioneering solar farming in Australia's Outback - Fullarton, Lex (SEGRA, 2019)
This paper outlines the development of dispersed, embedded solar pv systems in Western Australia in the early 2000s. Despite the introduction of renewable energy legislation in 2001, earlier Australian governments generally ignored renewable energy as a viable alternative to fossil fuel. That is except for the government of South Australia which was moving towards wind energy in the late 1990s.